Will antibiotic resistance sign the return of urethral dilators? - Steben, Marc (Brazilian Journal of Sexually Transmitted Diseases, 2016)
Before the availability of antibiotics, chronic urethritis meant regular — not so effective and rather painful — urethral irrigations. Frequently, chronic urethritis was complicated by urethral strictures, restricting urine and sperm flow. The treatment for such strictures was its dilation under minimal analgesia but major pain (Figure 1 and 2). For some patients, urethral dilation was to be done on a regular basis. The arrival of antibiotics meant the calvary of those men was over, but now, the threat of antibiotic resistance is upon us. [...]